2007
DOI: 10.1074/mcp.m700152-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Metal-coded Affinity Tag Approach to Quantitative Proteomics

Abstract: The quantitative analysis of protein mixtures is pivotal for the understanding of variations in the proteome of living systems. Therefore, approaches have been recently devised that generally allow the relative quantitative analysis of peptides and proteins. Here we present proof of concept of the new metal-coded affinity tag (MeCAT) technique, which allowed the quantitative determination of peptides and proteins. A macrocyclic metal chelate complex (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
197
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(201 citation statements)
references
References 29 publications
4
197
0
Order By: Relevance
“…However, CYP2E1 levels appear to be modulated to some extent by the compounds So far, the previous applications have been related to the labelling of antibodies used for immune-reactions, but in the following example it should be demonstrated that this procedure can also be applied for proteins directly, as it was discussed in a review article recently. 370 Ahrends et al 371,372 used metal-coded affinity tags (MeCAT) for direct labelling of standard proteins and eye lens proteins for quantitative ICP-SFMS. As MeCAT reagents they chose derivatives of the lanthanide chelating DOTA to which a cysteine reactive maleimide moiety was attached via a spacer.…”
Section: Speciation Analysismentioning
confidence: 99%
“…However, CYP2E1 levels appear to be modulated to some extent by the compounds So far, the previous applications have been related to the labelling of antibodies used for immune-reactions, but in the following example it should be demonstrated that this procedure can also be applied for proteins directly, as it was discussed in a review article recently. 370 Ahrends et al 371,372 used metal-coded affinity tags (MeCAT) for direct labelling of standard proteins and eye lens proteins for quantitative ICP-SFMS. As MeCAT reagents they chose derivatives of the lanthanide chelating DOTA to which a cysteine reactive maleimide moiety was attached via a spacer.…”
Section: Speciation Analysismentioning
confidence: 99%
“…In terms of flexibility, labeling with lanthanides using bi-functional chelating agents, which are covalently bound to the targeted bio molecule, and which form highly stable complexes with the metal ion, represents the current state of the art within this field. [33][34][35] Lanthanides are ideal elements for such labeling approaches because they can be detected with high sensitivity via ICP-MS due to a negligible background, as well as the absence of interferences.…”
Section: Introductionmentioning
confidence: 99%
“…199 A similar approach has been recently used for the absolute quantification of iodinated peptides using capillary LC hyphenated to ICP-MS. 32 During the last few years labeling using lanthanides and bi-functional chelating agents gained much interest and also represents the latest trend in ICP-MS based quantitative analysis. 24,27 Their application for absolute protein quantification, 35 multiplexed immunohistochemical detection of tumor markers, 200 peptide quantification, 201 or multiplexed bioassays 202 indicate the future potential of such labeling approaches.…”
mentioning
confidence: 99%
“…[26][27] For these reasons it has become a significant and complementary technique in bioanalysis for the determination of biomolecules and quantification of therapeutic agents. [28][29][30][31][32][33][34][35][36] Application of ICPMS allows the quantification of elements independent of their molecular form, hence the analyte retains its original form during quantification. Coupled with molecular information obtained from ESI-MS or MALDI enables the compound identification simultaneously with its quantification.…”
Section: Introductionmentioning
confidence: 99%